(untitled) (Journal of the College of Basic Education, 2025)
The commentators have taken great care in revealing the reasons for the Holy Quran’s preference for some words over others in Quranic usage, and among these interpreters is Sheikh Muhammad al-Tahir ibn Ashur, as these solutions occupied many places in his interpretation (al-Tahrir wa al-Tanwir), and based on that, this research came to clarify the reasons mentioned by Ibn Ashur for the preference of some verbs over others in Quranic usage, and the research was divided into two sections preceded by an introduction and a preface, as for the preface, it was dedicated to an introductory pause on the terms of preference and cause, and as for the two sections, the first of them dealt with the preference of verbs over others in terms of time, and the second section addressed the reasons for the preference of verbs over others in terms of form, and I benefited from multiple sources and references in writing this research, including books of interpretation in addition to books of language and grammar.